Custo de produção e rentabilidade de abacaxizeiro cv. pérola em Cassilândia (MS), sob diferentes doses de potássio - dos Reis, Luis Lessi [UNESP]; Anselmo Tarsitano, Maria Aparecida; Hiraki, Simone Silva [UNESP]; Bardiviesso, Diogenes Martins [UNESP] (Universidade Federal de Uberlândia (UFU), 2012)
The pineapple crop are high potential for economic expression and social, but problems with productivity and management of production costs can be solved in order to ensure the sustainability of the farming system. The objective of this study was determine the cost of production and profitability of the pineapple's cultivation Pearl in Cassilandia-MS, under application of potassium doses fertilizer. The treatments consisted of the following doses of potassium (K2O): 0, 200, 400, 600, 800 kg ha(-1), used as a commercial source of potassium chloride (60% K2O). Were determined by estimating the effective operational cost (EOC), total operating cost (TOC), gross (RB), operating profitability (LO), profitability index (%), productivity of balance and equilibrium price. It was found that all treatments had operating profitability and positive profitability index. Potassium fertilization with 200 kg ha(-1) gave an average productivity of 50416.58 kg ha(-1), and also promoted the highest operating profit of R$ 9,108.97, the profit margin of 36.13% and best benefit cost (R$ 1.57).

A cultura do abacaxi possui elevado potencial de expressão econômica e social, uma vez que problemas relacionados a produtividade e o gerenciamento dos custos de produção sejam solucionados de maneira a garantir a sustentabilidade do sistema. O objetivo deste trabalho foi determinar o custo de produção e rentabilidade da cultura do abacaxi ‘pérola’, em da aplicação de diferentes tratamentos da adubação potássica. Os tratamentos foram constituídos das seguintes doses de potássio (K2O): 0, 200, 400, 600, 800 kg ha-1, utilizado como fonte comercial o cloreto de potássio (60% de K2O). Foram determinados por estimação o custo operacional efetivo (COE), custo operacional total (COT), receita bruta (RB), lucratividade operacional (LO), índice de lucratividade (%), produtividade de equilíbrio e preço de equilíbrio. Constatou-se que todos os tratamentos apresentaram lucratividade operacional e índice de lucratividade positivos, muito embora o uso racional com 200 kg ha-1 de K2O promoveu lucro operacional de R$ 9108,97.
Cost of production and profitability of pineapple ‘pérola’ cv. in Cassilândia, state of Mato Grosso do Sul, under different doses
Keywords: Ananas comosus (L); Merril; Economic analysis; Management; Productivity; Fruit quality